If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + -16 = 17 Reorder the terms: -16 + 3w = 17 Solving -16 + 3w = 17 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 3w = 17 + 16 Combine like terms: -16 + 16 = 0 0 + 3w = 17 + 16 3w = 17 + 16 Combine like terms: 17 + 16 = 33 3w = 33 Divide each side by '3'. w = 11 Simplifying w = 11
| 36=-39 | | 36=-36 | | 4*e=24 | | h^2+11h+121= | | 19=x-10 | | 18x-20x= | | k-6=12 | | -28-x=2(x-2)-6 | | -58+108= | | -30=2x-6 | | 3x^2+60=4x^2+17x | | 8x-6=9+5 | | 2(3x+5)=-4 | | g(x)=12x | | (3x+y)=4 | | -3-5y=4+3y+7-8y | | 6=y-44 | | y=(x^4-3)(x^2+2) | | 9x+10-8x=14 | | 9-(6x+4)=21-8x | | 12+-9=14 | | (5/9)n-2=(2/3)n | | (3x^2)(-2x^4)= | | 4b+5=2b-14 | | 2(5x+20)+2(2x+4)=216 | | -8+18=m-6 | | 6x+12-2x=2x+8 | | 21z-20z=-15-14 | | 6x+2=4x-12 | | 3(x+4)-8=5x-6 | | f(t)=4t+3t^3+2t-7 | | 8x+7=43-2x |